Pengaruh Sarana Prasarana Dan Disiplin Kerja Terhadap Kinerja Pegawai Dinas Pemadam Kebakaran Kota Bekasi - Novita Syahidah Sari; Sugeng Suroso; Ery Teguh Prasetyo (JURNAL RUMPUN MANAJEMEN DAN EKONOMI, 2024)
This research aims to determine the influence of infrastructure and work discipline on the performance of Bekasi City Fire Department employees. The research method used is quantitative research, where this research is used to examine certain populations and samples, data collection uses research instruments, quantitative or statistical data analysis, aims to test predetermined hypotheses. The sampling technique used was saturated sampling technique or the entire population was sampled. The population in this study was 55 respondents. Data analysis uses Smart PLS 4.0 software and hypothesis testing, namely the t test and F test. Based on the results of the path coefficient hypothesis test, there are P-values ​​of 0.000 or < 0.05 and the t-statistics value of infrastructure has a value of 5,713 or > 1.96, it is stated that there is a significant influence between the infrastructure variables on employee performance. Based on the results of the path coefficient hypothesis test, there is a P-value of 0.002 or <0.05 and the t-statistics value of work discipline has a value of 3,080 or > 1.96, so it is stated that there is a significant influence between the work discipline variable on employee performance.